NEUROPATI OPTIK BILATERAL PASCA TERAPI ETAMBUTOL - Josephina, Sarah M.; Walandow, Denny (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Ethambutol is one of the oral anti-tuberculosis drugs frequently used. Although its side effect like optic neuropathy is rare, it can be harmful to the vision. The mechanism of optic neuropathy is not clearly understood, but it might be related to the dose and duration of ethambutol treatment. We reported a case of a 60-year-old female who came to the hospital with blurred vision for the previous month. She had undergone a pulmonary tuberculosis treatment with ethambutol for six months. The ophthalmologic examination showed visual acuity of the right eye (OD) 2/60, visual acuity of the left eye (OS) 1/60 with a good projection; the IOP of OD was 17.3 mm Hg and of OS 20.6 mm Hg; lens opacity C1P2. The funduscopy of OD revealed a distinct optic disc border and a temporally pale disc color; a positive foveal reflex; and in the retina we found drusen, arteriosclerosis, and a crossing phenomenon. The funduscopy of OS revealed a non-uniform fundus reflex; a distinct optic disc border; the optic disc colour was paler than that of OD; a positive foveal reflex; and in the retina we found drusen, arteriosclerosis, and a crossing phenomenon. The RAPD was not found and the Amsler Grid tests were normal for both eyes. The Ishihara tests showed positive colour blindness in both eyes and the perimetry tests showed a defect in the central and temporal vision of both eyes. Conclusion: Based on all the tests performed, the diagnosis of this patient was bilateral optic neuropathy due to ethambutol, accompanied with hypertensive retinopathy degree 2. Keywords: blurred vision, optic neuropathy, ethambutol. Abstrak: Etambutol merupakan salah satu obat anti-tuberkulosis yang cukup aman. Efek sampingnya yaitu neuropati optik jarang terjadi, tetapi berakibat buruk. Mekanisme neuropati optik masih belum diketahui tetapi diduga berhubungan dengan dosis dan durasi pemakaian etambutol. Kami melaporkan kasus seorang wanita suku Minahasa berusia 60 tahun dengan diagnosis neuropati optik bilateral pasca terapi etambutol. Keluhan utama mata kabur telah dirasakan sejak satu bulan lalu. Riwayat pasca terapi tuberkulosis dengan etambutol setahun yang lalu. Pada pemeriksaan oftalmologik didapatkan visus mata kanan (VOD) 2/60 dan visus mata kiri (VOS) 1/60, pinhole (-) pada kedua mata, dan proyeksi baik segala arah. Tekanan intra okular OD 17,3 mm Hg dan OS 20,6 mm Hg, lensa agak keruh (C1P2). Pemeriksaan funduskopi OD memperlihatkan papil nervus optikus berbatas tegas dan berwarna agak pucat terutama pada bagian temporal; pada retina terdapat drusen, arteriosklerosis, crossing phenomenon; dan refleks fovea positif. Pada pemeriksaan funduskopi OS didapatkan refleks fundus positif non uniform; papil nervus optikus berbatas tegas dan berwarna lebih pucat daripada papil mata kanan; pada retina terdapat drusen, arteriosklerosis, crossing phenomenon, dan refleks fovea positif. RAPD tidak ditemukan sedangkan pemeriksaan Amsler Grid tampak normal pada kedua mata. Pemeriksaan Ishihara pada kedua mata didapatkan buta warna. Pada perimetri kedua mata didapatkan defek pada lapang pandang sentral dan temporal. Simpulan: Berdasarkan hasil pemeriksaan yang dilakukan, diagnosis pasien ialah neuropati optik bilateral akibat etambutol, yang disertai retinopati hipertensi derajat 2. Kata kunci: kekaburan, neuropati optik, etambutol.